Informal Payments for Health Care in Iran: Results of a Qualitative Study - Mojtaba Parsa; Kiarash Aramesh; Saharnaz Nedjat; Mohammad Jafar Kandi; Bagher Larijani (Tehran University of Medical Sciences, 2015)
Background: Informal payments to health care providers have been reported in many African, Asian and European countries. This study aimed to investigate different aspects of these payments that are also known as under-the-table payments in Iran. Methods: This is an in-depth interview-based qualitative study conducted on 12 purposively chosen clinical specialists. The interviewees answered 9 questions including the ones about, definitions of informal payments, the specialties and hospitals mostly involved with the problem, how they are paid, factors involved, motivation of patients for the payments, impact of the payments on the health care system and physician-patient relationship and the ways to face up with the problem. The findings of the study were analyzed using qualitative content analysis method. Results: Six topics were extracted from the interviews including definitions, commonness, varieties, motivations, outcomes and preventive measures. It was revealed that under-the-table payments are the money taken (either in private or public portions) from patients in addition to what formally is determined. This problem is mostly seen in surgical services and the most important reason for it is unrealistic tariffs. Conclusion: Regarding the soaring commonness of informal payments rooted in underpayments of health expenditures in some specialties, which deeply affect the poor, the government has to boost the capitation and to invest on health sectors through supporting the health insurance companies and actualizing the health care costs in accord with the real price of the health care delivered.